2004
DOI: 10.1021/es0496219
|View full text |Cite
|
Sign up to set email alerts
|

NO2 Emissions from Agricultural Burning in São Paulo, Brazil

Abstract: We report here on the application of a compact ultraviolet spectrometer to measurement of NO2 emissions from sugar cane field burns in São Paulo, Brazil. The time-resolved NO2 emission from a 10 ha plot peaked at about 240 g (NO2) s(-1), and amounted to a total yield of approximately 50 kg of N, or about 0.5 g (N) m(-2). Emission of N as NOx (i.e., NO + NO2) was estimated at 2.5 g (N) m(-2), equivalent to 30% of applied fertilizer nitrogen. The corresponding annual emission of NOx nitrogen from São Paulo State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…Gas emissions to the atmosphere are another aspect of atmospheric pollution associated with sugarcane burning. In sugarcane areas, concentrations of CO and O 3 are commonly high (Kirchoff et al 1991), while nitrogen oxides (NOx) emissions reached 25 kg N/ha (Oppenheimer et al 2004). Part of the N lost to the atmosphere during burning of sugarcane fields returns to the Earth's surface via wet and dry deposition.…”
Section: Environmental Consequences Of Sugarcane Burningmentioning
confidence: 99%
“…Gas emissions to the atmosphere are another aspect of atmospheric pollution associated with sugarcane burning. In sugarcane areas, concentrations of CO and O 3 are commonly high (Kirchoff et al 1991), while nitrogen oxides (NOx) emissions reached 25 kg N/ha (Oppenheimer et al 2004). Part of the N lost to the atmosphere during burning of sugarcane fields returns to the Earth's surface via wet and dry deposition.…”
Section: Environmental Consequences Of Sugarcane Burningmentioning
confidence: 99%
“…Agricultural waste burning, particularly of sugarcane fields, is the main source of fire emissions in agricultural areas in the south of Brazil (Lara et al, 2005). Openheimer et al (2004) observed emission factors for NO 2 of 1.3 g NO 2 kg −1 dry matter for sugarcane burning in São Paolo. Taking a ratio of NO : NO 2 of 85 : 15 as suggested in their paper would imply a NO x emission factor of 5.7 g NO kg −1 dry matter.…”
Section: Introductionmentioning
confidence: 97%
“…This knowledge has been updated in more recent studies, such as Christian et al [22] which is concerned with savanna fires, Yokelson et al [23,24] and Soares Neto et al [25,26] which assemble information about fire emissions in tropical vegetation associated with pasture maintenance and deforestation, based on laboratory experiments and field campaigns, and Akagi et al [27] which present emission factors, among other information, for fourteen types of vegetation. Although some studies have treated different aspects of sugarcane straw burning [28][29][30][31][32], specific information about emission factors for species emitted during pre-harvest burning is still scarce, especially specific to Brazil. It is common modeling practice to use the generic emission factors for savanna, pasture or agricultural wastes, such as those provided by Andreae and Merlet [21] and IPCC [33] for the estimation of emissions associated with sugarcane straw burning.…”
Section: Introductionmentioning
confidence: 99%